Pengaruh Pemberiaan Air Kelapa Hijau Terhadap Penurunan Nyeri Dismenore Primer pada Remaja Putri di Pesantren Daarul Ahsan Jayanti Tangerang - Lulu Ul Puadiah; Maryati Sutarno (Malahayati Nursing Journal, 2023)
ABSTRACT Menstruation is the process of blood discharge from the vagina that occurs due to the natural monthly cycle in the woman's body. This cycle is a process of reproductive pragan Women to prepare in case of pregnancy. This preparation is characterized by a thickening of the walls of the Uterine (endometrium) containing blood vessels. If pregnancy does not occur, the endometrium will decay and come out with blood through the vagina. Primary dysmenorrhea is menstrual pain that is found without abnormalities in the genital apparatus. The nature of pain is infectious seizures, usually limited to the lower abdomen, but can spread to the lumbar and thigh regions. Along with the pain can also be found nausea, vomiting, headache, diarrhea, and so on. To find out the effect of giving green coconut water to reducing primary dysmenorrhea in young women at Daarul Ahsan Jayanti Islamic Boarding School Tangerang in 2022. The research design used is quantitative research with a cross-sectional research design. Cross sectional research design is a study to study a correlation dynamics between risk factors and effects, and with an approach, observation or with data collection at a certain time. There was a significant relationship between Before and After being given Green Young Coconut Water, it was found that 69 respondents before being carried out green young coconut water experienced moderate pain as many as 52 respondents (75.4%), severe pain 17 respondents (24.6%). Meanwhile, after being given light green coconut water, 50 respondents (72.5%) mild pain (72.5%) and moderate pain were found in 19 respondents (27.5%). Based on the results of the Wilcoxon test, it shows that the Median, star, deviation, drink and maximum posttest values are smaller than the Pretest and p values = 0.000. The value of p 0.05 then H0 is rejected and Ha is accepted, meaning that there is an influence of giving green young coconut water on dysmenorrhea in Pesantren Daarul Ahsan Jayanti.There is an effect of giving young green coconut water on dysminore pain in adolescents, researchers advise adolescents who experience menstrual pain to consume green young coconut water at the time of the first day of menstruation.  Keywords: Stunting, Exclusive Breastfeeding, Infectious Disease, Parity, History of CED During Pregnancy    ABSTRAK Menstruasi adalah proses keluarnya darah dari vagina yang terjadi diakibatkan siklus bulanan alami pada tubuh Wanita. Siklus ini merupakan proses pragan reproduksi Wanita untuk bersiap jika terjadi kehamilan. Persiapan ini ditandai dengan penebalan dinding Rahim (endometrium) yang berisi pembuluh darah. Jika tidak terjadi kehamilan, endometrium akan mengalami peluruhan dan keluar Bersama darah melalui vagina. Dismenore primer merupakan dismenore yang dijumpai tanpa kelainan pada alat-alat genital yang nyata. Sifat rasa nyeri ialah kejang berjangkit-jangkit, biasanya terbatas pada perut bawah, tetapi dapat menyebar ke daerah pinggang dan paha. Bersamaan dengan rasa nyeri dapat pula dijumpai rasa mual, muntah, sakit kepala, diare, dan sebagainya.  Dapat Mengetahui pengaruh pemberian  air kelapa  hijau terhadap penurunan dismenore primer pada remaja putri di Pesantren Daarul Ahsan Jayanti Tangerang Tahun 2022. Desain penelitian yang digunakan adalah penelitian kuantitatif dengan desain penelitian menggukan Cross sectional. Desain penelitian Cross sectional  merupakan suatu penelitian untuk mempelajari suatu dinamika kolerasi antara faktor-faktor resiko dengan efek, dan dengan suatu pendekatan, observasi ataupun dengan pengumpulan data pada suatu saat tertentu. Terdapat hubungan yang signifikan antara Sebelum dan Sesudah diberikan Air Kelapa Muda Hijau, didapatkan 69 responden sebelum dilakukan  air kelapa muda hijau mengalami nyeri sedang sebanyak 52 responden (75,4%), nyeri berat 17 responden (24,6%). Sedangkan setelah diberikan  air kelapa hijau muda didapatkan yang nyeri ringan 50 responden (72,5%) dan nyeri sedang 19 responden (27,5%). Berdasarkan hasil uji Wilcoxon menunjukkan nilai Median, star, deviation, minum dan maksimum posttest lebih kecil dari pada Pretest dan nilai p=0,000. Nilai p 0,05 maka H0 di tolak dan Ha diterima, artinya ada pengaruh pemberian  air kelapa muda hijau terhadap Dismenore di Pesantren Daarul Ahsan Jayanti. Riwayat Ada pengaruh pemberian air kelapa muda hijau terhadap nyeri dysminore pada remaja, peneliti menyarankan pada remaja yang mengalami dismenore untuk mengkonsumsi air kelapa muda hijau pada saat menstruasi hari pertama Kata Kunci: Air Kelapa Hijau, Dismenore, Remaja Putri